Pengembangan Ekowisata Pulau Tunda Berbasis Komunitas dalam Era Industri 4.0 - Helmy Faizi Bahrul Ulumi; Muhammad Syafar (Universitas Andalas, 2021)
The development agenda that designed in the Sustainable Development Goals (SDGs) in 2030 is a challenge for all global stakeholders. This article aims: 1) To identify ecotourism that is develop based on the social capital and local wisdom of community in Tunda Island, 2) To identify the development of community-based ecotourism in the industrial era 4.0 through digital technology, 3) To analyse of benefits of digital technology for ecotourism development. The method used through field study with descriptive qualitative research type. The results of the study show that are: 1) ecotourism that has been developed by the community focuses on social capital and local wisdom of the community, 2) Digital technology application on the implementation of ecotourism development conducted through the provision of websites and social media by community of Tunda island, and 3) Benefit of digital technology has an impact for socio-economic of community and acessability dealing with ecotourism management. Furthermore, enhaching human capacity needed for community to improve Tourism Group (Pokdarwis) as a social institution that has a role in developing ecotourism in Tunda Island.